Comparison of aero-bars versus traditional cycling postures on physiological parameters during submaximal cycling - Sheel, A. W.; Lama, I.; Potvin, P.; Coutts, K. D.; McKenzie, D. C. (Canadian Journal of Applied Physiology, 1996)
The purpose of this investigation was to quantify the difference in energy expenditure between traditional cycling handlebars and aero-bars during outdoor submaximal cycling. Eleven trained cyclists (age = 29.3 +/- 1.9 years, weight = 69.4 +/- 3.8 kg, VO2max = 58.1 +/- 2.0 ml.kg-1.min-1) were randomly assigned a sequence of three hand positions: brake hoods (BH), drop-bars (DB), and aero-bars (AB). Subjects cycled at 30 km.h-1 in one position for 5 minutes, then recovered until HR fell below 120 bpm. This was then repeated for the other hand positions. All cycling was completed on a standard racing bike fitted with aero-bars. Tire pressure was held constant for all trials. A portable telemetric system (Cosmed K-2) was used to measure VO2, VE and heart rate (HR) during the trials. No statistical differences were observed between AB and DB. Significant differences (p < .05) were found between BH (VE = 66.1 +/- 2.7 L.min-1; HR = 152 +/- 4 bpm; VO2 = 1.56 +/- .15 L.min-1) and AB (VE = 61.3 +/- 2.8 L.min-1; HR = 146 +/- 4 bpm; VO2 = 1.31 +/- .10 L.min-1). AB provides an energy savings over the traditional BH cycling posture.